The Utilization of Volcanic Ash in Medium Fired Stoneware Ceramic Body - Rohmat Sulistya; Wahyu Gatot Budiyanto (Balai Besar Keramik, 2020)
The aims of this research are to develop a medium fired stoneware body (1150oC-1250oC) as well as a prototype of glazed ceramic products based on several local clays using volcanic ash. The developed clay comes from Sukabumi, Singkawang, Bojonegoro and Malang. Research includes analysis of raw materials, development of stoneware ceramic bodies, testing of physical properties of ceramic bodies, determination of optimum ceramic bodies and development of prototype products. Raw material analysis consists of mineral analysis using XRD and Atomic Absorption Spectroscopy (AAS). Ceramic body development was carried out by the line blend method followed by testing plasticity, shrinkage, porosity and fracture strength. Prototype product development was carried out on optimum ceramic bodies composition. The results showed volcanic ash can be used to develop local clay-based ceramic stoneware bodies from Sukabumi, Bojonegoro and Malang which optimum ceramic bodies coded as Sb-2, Sb-3, Sb-4, Sb-5, Bn-5, Ml-4 and Ml-5 with volcanic ash percentage of 10%-40%. In this research, the optimum composition for Singkawang clay has not yet been found. However, opaq, matt and celadon glazes that applied to the optimum ceramic body resulted good and decent prototype products